The Effect of Profitability, Leverage, and Institutional Ownership on the Firm Value of Transportation Companies Listed on the Indonesia Stock Exchange - Baskara, Ida Bagus Reri Mahesa; Ida Bagus Putra Astika (E-Jurnal Akuntansi, 2025)
Firm value is a market value that can provide prosperity to shareholders. They want the market price of the companies under their control to increase. They need fundamental company information such as information about the company's profitability, leverage or capital structure of institutional ownership, and use that information to make decisions or release shares that they already hold. This study aims to obtain empirical evidence of the effect of profitability, leverage, and institutional ownership on the value of transportation companies listed on the Indonesia Stock Exchange 2010-2014. The number of samples, using a purposive sampling method of 14 companies from 33 companies so that the total observations obtained were 70 observations. The data analysis technique used in this study is multiple linear regression. The results of the analysis prove that profitability and institutional ownership have a positive effect and leverage has a negative effect on the value of transportation companies listed on the Indonesia Stock Exchange.